Construction of a Prognostic Score for Ultrasound Evaluation of the Transobturator Sling for Stress Urinary Incontinence - Espada-González, Cristina; Sabonet-Morente, Lorena; Pérez-González, Rita María; González-Mesa, Ernesto Santiago; Jiménez-López, Jesús Salvador (MDPI, 2022)
Currently, pelvic floor ultrasound allows us to correctly visualize the synthetic material used in stress urinary incontinence surgery. The objective of this study is the construction of a score and its correlation with the SUU clinic. During the study period, 81 patients with transobturator slings were studied using ultrasound. Through multivariate analysis, the statistically significant variables were the distance from the sling to the urethral wall (p = 0.004), the shape of the sling at rest (p = 0.003), and the symmetry of the mesh (p = 0.016). Through these variables, the construction of a score was carried out. Once the model was constructed, its internal validation was carried out to determine the discrimination capacity of patients who present clinical stress and those who do not, with an area under the curve of 0.848 (95% CI (0.72–0.97), p < 0.001). This simple score using three ultrasound variables serves to adequately and objectively discriminate patients who have successful surgery and absence of clinical effort.
Keywords: Incontinencia urinaria; Stress urine incontinence; Anti-incontinence sling; Anti-incontinence surgery; Pelvic floor ultrasound